Multi-Tier Blockchain-Based Land Registry Using Fog Computing - Ashank Priyadarshi; Thankaraja Raja Sree (IEEE Access)
The conventional method of selling and purchasing land has several drawbacks because it requires a lot of time, a lengthy verification procedure, and prolonged final processing. Various blockchain-based solutions have been implemented to tackle the problems of the existing land record. The government of India is currently developing its blockchain-based network to store and verify land records. The solutions cannot handle large amounts of hard-copy documents and rely on a single-tier block network, which affects integrity and decentralization. In this paper, we address the existing problem by introducing a blockchain network at the ground level for monitored lands. Each country will have an associated device as part of the blockchain network to carry out the verification process, thereby distributing the control and workload across two tiers. The devices will interact using the concept of fog computing over the decentralized blockchain network, forming a peer-to-peer network. The proposed solution is compared with an existing solution in terms of cost, computational time complexity, and overall computation cost.